1997
DOI: 10.1002/(sici)1097-0142(19971115)80:10<1897::aid-cncr4>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C inhibits the growth of a bacterial risk factor for gastric carcinoma: Helicobacter pylori

Abstract: High doses of vitamin C inhibit the growth of H. pylori in vitro as well as in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 0 publications
3
76
2
1
Order By: Relevance
“…A possible relation between H. pylori infection and ascorbic acid is under investigation, as some research has indicated that high-dose vitamin C is effective in inhibiting H. pylori infection [41,42].…”
Section: Vitamin C (Ascorbic Acid)mentioning
confidence: 99%
“…A possible relation between H. pylori infection and ascorbic acid is under investigation, as some research has indicated that high-dose vitamin C is effective in inhibiting H. pylori infection [41,42].…”
Section: Vitamin C (Ascorbic Acid)mentioning
confidence: 99%
“…It has been reported that α-tocopherol could ameliorate the aggravation of stress-associated gastric mucosal damage (25). In in vivo assays, the consumption of vitamins C and E could reduce the gastric H. pylori loads in animal models (26)(27)(28)(29). Sies et al (30) showed that the concentrations of α-tocopherol in H. pylori-negative subjects were higher in the corpus than in the antrum or duodenum.…”
Section: Resultsmentioning
confidence: 99%
“…In our data, we did not observe a statistically significant interaction between dietary intake of vitamin C (or plasma concentration of vitamin C) and processed meat intake. Another potential mechanism is that vitamin C may act by inhibiting or slowing the infection and growth of H. pylori in the gastric mucosa (Pal et al 2011;Zhang et al 1997). Weaknesses of our study include potential misclassification of dietary intake of foods containing vitamin C (and lack of information on use of dietary supplements) and imprecision in plasma vitamin C measurements.…”
Section: Discussionmentioning
confidence: 99%
“…infection in the gastric mucosa has been associated with pro-inflammatory responses and mucosal proliferation, as well as lower vitamin C levels in blood and gastric juice, possibly due to malabsorption or decreased stability and bioavailability (Lahner et al 2012). In addition, very high doses of vitamin C may inhibit H. pylori infection, growth, and reinfection (Pal et al 2011;Zhang et al 1997). As a consequence, the multistep process of gastric cancer carcinogenesis involving chronic H. pylori infection may be slowed or partially reversed in some individuals with high intake of vitamin C.…”
Section: Introductionmentioning
confidence: 99%